Social capital and investment in R&D: new externalities - Sequeira, Tiago Neves; Ferreira-Lopes, Alexandra (Journal of Business Economics and Management, 2013)
We introduce social capital in an endogenous growth model with physical capital, human capital, and research and development (R&D), and we compare the market with the efficient solutions. As social capital is not tradable in the market and since it favours research networks, it introduces new externalities in this framework. These externalities induce the market to invest less in social capital than would a social planner and decrease the tendency to underinvestment in R&D. We quantify the distortions in the model. In some conditions, the new distortions are strong enough to overcome the usual result of underinvestment in R&D.